Planar bifunctional Luneburg-fisheye lens made of an anisotropic metasurface - Wan, Xiang (2016)
Luneburg lens and Maxwell-fisheye lens are well-known microwave and optical devices with distinct focusing properties. Here, a planar bifunctional Luneburg-fisheye lens made of an anisotropic metasurface is presented, which features as a Luneburg along the horizontal optical axis, while as a fisheye along the vertical optical axis. A method to control the inhomogeneous indices of refraction along the two optical axes independently is proposed by designing an anisotropic and nonuniform metasurface, which can provide the required distributions of refractive indices approximately for Luneburg and fisheye lenses viewing from the two optical axes. Experiments in the microwave frequency range demonstrate very good performance of the planar bifunctional Luneburg-fisheye lens. The proposed method opens up an avenue to design other kinds of bifunctional devices using metasurfaces in the microwave, terahertz, and even optical ranges.